The capitalist system in the context of migrant and refugee workers: the sisyphus myth (Research, Society and Development, 2020)
In front of an international context of humanitarian crises, more than ever before, it is noticeable the wave of migrants and refugees who, fleeing war, hunger and misery, are seeking new destinations and realities in countries with less drastic political and social conjectures. However, when they reach new lands, their reception is not always hospitable. Because they are vulnerable, from their point of origin, fleeing violence and extreme poverty, desperate to gain stability in a new country, refugees and especially illegal immigrants are in “perfect” conditions to be introduced in extremely precarious labour situations, or even analogous to slavery. Thus, from bibliographic survey, through the hypothetical-deductive method, this article aims to point out how the crises of capitalism are cyclical, being created by itself, to the point of reinventing itself while workers, especially under the above conditions, are even more harmed. Therefore, it demonstrates the conditions under which extremely vulnerable migrant and refugee workers are subjected to labour exploitation, seeking to point out how the current capitalist dynamic is fed back by contemporary slavery.Incluir o resumo em inglês.